Gas-Phase Tyrosine-to-cysteine Radical Migration in Model Systems. Issue 3 (June 2015) - Lesslie, Michael; Osburn, Sandra; van Stipdonk, Michael J; Ryzhov, Victor
Radical migration, both intramolecular and intermolecular, from the tyrosine phenoxyl radical Tyr(O ) to the cysteine radical Cys(S ) in model peptide systems was observed in the gas phase. Ion–molecule reactions (IMRs) between the radical cation of homotyrosine and propyl thiol resulted in a fast hydrogen atom transfer. In addition, radical cations of the peptide LysTyrCys were formed via two different methods, affording regiospecific production of Tyr(O ) or Cys(S ) radicals. Collision-induced dissociation of these isomeric species displayed evidence of radical migration from the oxygen to sulfur, but not for the reverse process. This was supported by theoretical calculations, which showed the Cys(S ) radical slightly lower in energy than the Tyr(O ) isomer. IMRs of the LysTyrCys radical cation with allyl iodide further confirmed these findings. A mechanism for radical migration involving a proton shuttle by the C-terminal carboxylic group is proposed.